P135 Intermittent theta burst increases action potential threshold and spike firing in cortical layer 5 pyramidal neurons. Issue 3 (March 2017) - Tang, A.; Hong, I.; Boddington, L.; Reynolds, J.; Garrett, A.; Etherington, S.; Rodger, J.
Abstract : Introduction: Repetitive transcranial magnetic stimulation has become a popular method of inducing neural plasticity in humans. In particular, complex patterned stimulation such as intermittent theta burst stimulation (iTBS) is routinely used to increase corticospinal excitably. Despite its wide use, the mechanisms underlying iTBS-induced increases in corticospinal excitability remain unclear. Objectives: Experimental (acute brain slices) models of repetitive magnetic stimulation (rMS) allow for direct investigation of iTBS-induced plasticity, such as changes at the single neuron level. Here we investigated whether iTBS rMS alters the active and passive electrophysiological properties of layer 5 pyramidal neurons in the juvenile mouse cortex. Materials & methods: Acute brain slices were prepared from the motor and somatosensory cortex of P12-P15 C57Bl6J mice. rMS was delivered with a custom circular coil (8 mm diameter) placed underneath the perfusion bath and slice. Whole cell current clamp recordings were made from layer 5 pyramidal neurons to characterise (i) passive membrane properties (resting membrane potential, input resistance) (ii) active membrane properties (action potential threshold, rheobase) and (iii) spike firing. Baseline recordings were followed by 192s of control (n = 10/9 animals) or iTBS rMS (n = 9/7 animals). Recordings were made immediately post stimulation and again after 10 and 20 min. Results: ITBS did not alter the resting membrane potential (p = 0.464) or input resistance (p = 0.418) of layer 5 pyramidal neurons. Interestingly, iTBS increased action potential threshold relative to baseline (control 1.855 mV ± 1.098 vs iTBS −1.537 mV ± 1.158, p = 0.048) but did not alter the rheobase current (p = 0.328). iTBS also increased the number of action potentials (spike firing) generated in response to suprathreshold currents (control 0.783 Hz ± 0.426 vs iTBS 3.167 Hz ± 0.449 p = 0.001). Conclusion: Our data suggest that rTMS-induced plasticity may be in part due to electrophysiological changes at the single neuron level, such as altered action potential thresholds and spike firing. These results help elucidate the mechanisms of rTMS-induced plasticity which is essential for the optimisation of rTMS treatment in health and disease.